2018
DOI: 10.1159/000489852
|View full text |Cite
|
Sign up to set email alerts
|

The 72Pro Variant of the Tumor Protein 53 Is Associated with an Increased Breast Cancer Risk in the Moroccan Population

Abstract: Background: The purpose of our case control study is to explore the potential association of tumor protein 53 (TP53) c.215G>C, p. (Arg72Pro) polymorphism (rs1042522) with the risk of breast cancer (BC) development in the Moroccan population. Methods and Results: The study population consisted of 125 female patients with confirmed BC and 126 healthy controls. DNA samples were genotyped by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism assay method using BstUI restriction enzyme. We showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
4
8
0
Order By: Relevance
“…In the subgroup analysis, our meta-analysis revealed a high risk of breast cancer with TP53 p.Arg72Pro in Caucasians (dominant model and additive model) and Africans (recessive and additive models). These trends were consistent with previous studies [12,13,22] but inconsistent with the findings of other studies [52,53]. However, Jafrin et al 2020 concluded that TP53 p.Arg/Pro was associated with the risk of breast cancer in the South Asian population.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the subgroup analysis, our meta-analysis revealed a high risk of breast cancer with TP53 p.Arg72Pro in Caucasians (dominant model and additive model) and Africans (recessive and additive models). These trends were consistent with previous studies [12,13,22] but inconsistent with the findings of other studies [52,53]. However, Jafrin et al 2020 concluded that TP53 p.Arg/Pro was associated with the risk of breast cancer in the South Asian population.…”
Section: Discussionsupporting
confidence: 70%
“…Genotype distribution of the control population that met HWE was a minimum requirement for studies to be retained for the meta-analysis. Out of the 21 studies (7841cases and8876 controls), eleven were Caucasians [12-14, 23-28, 36, 37], nine were Asians [21,[29][30][31][32][33][34][35]38] and one was African [22] (Table 1). Table 2 shows pooled ORs and heterogeneity testresults of the association between the TP53 p.Arg72Pro polymorphism and the risk of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the subgroup analysis, our metaanalysis revealed a high risk of breast cancer with TP53 p.Arg72Pro in Caucasians (dominant model and additive model) and Africans (recessive and additive models). These trends were consistent with previous studies [12,13,38] but inconsistent with the ndings of other studies [52,53]. However, Jafrin et al 2020 concluded that TP53 p.Arg/Pro was associated with the risk of breast cancer in the South Asian population.…”
Section: Discussionsupporting
confidence: 66%
“…Genotype distribution of the control population that met HWE was a minimum requirement for studies to be retained for the metaanalysis. Out of the 21 studies (7841cases and8876 controls), eleven were Caucasians [12][13][14][21][22][23][24][25][26][27][28], nine were Asians [29][30][31][32][33][34][35][36][37] and one was African [38] (Table 1). Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…1) that investigated the association of p.Arg72Pro of P53 gene in the context of breast cancer were included, of which only 55 studies had a genotype distribution of control population that met Hardy-Weinberg equilibrium, and 21 out of the 55 studies have cases age-matched controls (Table 1). Among these studies, the participants of 9 studies were Europeans [12][13][14][21][22][23][24][25][26], 9 studies were Asians [27-35], 2 were Americans [36,37]. Genotype distribution of the control population that met Hardy-Weinberg equilibrium was a minimum requirement for studies to be included.…”
Section: Resultsmentioning
confidence: 99%